Anti‐inflammatory and anti‐bacterial properties of tetramethylhexadecenyl succinyl cysteine (TSC): a skin‐protecting cosmetic functional ingredient. (22nd October 2014) - Fernandéz, J. R.; Rouzard, K.; Voronkov, M.; Huber, K. L.; Stock, J. B.; Stock, M.; Gordon, J. S.; Pérez, E.
Synopsis Background The skin is the first line of defence against exposure to microbial, physical, environmental and chemical insults. In mobilizing a protective response, several different cell types located in our skin release and respond to pro‐inflammatory cytokines ensuring skin homeostasis and health. However, chronic activation of this response eventually causes damage resulting in premature ageing. Diosodium tetramethylhexadecenyl succinyl cysteine (TSC or SIG1273), an isoprenylcysteine small molecule, down modulates these inflammatory signalling pathways in various cell types (keratinocytes, peripheral blood mononuclear cells (PBMCs) and endothelial cells) and possesses anti‐bacterial properties. Thus, TSC represents a novel cosmetic functional ingredient that provides a broad spectrum of benefits for the skin. Objective To assess the anti‐inflammatory properties of TSC in several cutaneous cell types and further investigate its anti‐microbial activity. Methods Cultured normal human epidermal keratinocytes were exposed to chemical irritant phorbol 12‐myrisate 13‐acetate (TPA) or ultraviolet‐B light (UVB) to induce pro‐inflammatory cytokine (IL‐6, IL‐8 and TNF‐α) production. T‐cell receptor (TCR) activation of PBMCs and nickel (Ni2+) treatments of human dermal microvascular endothelial cells (HDMECs) were performed resulting in IL‐4, IL‐6, IL‐8 and IL‐17 production. Streptococcus pyogenes were cultured to determine minimal inhibitory concentration values. Results In vitro studies demonstrate TSC blocks TPA and UVB‐induced cytokine production in cultured keratinocytes. Similarly, TSC inhibits overproduction of IL‐4 and IL‐17 in T‐cell receptor (TCR)‐activated PBMCs as well as nickel induction of IL‐6 and IL‐8 in HDMECs. Lastly, TSC demonstrated anti‐microbial properties, inhibiting cell growth of S. pyogenes. Conclusions Tetramethylhexadecenyl succinyl cysteine represents a novel cosmetic functional ingredient that provides a dual modulating benefit of skin protection to individuals by reducing inflammation in keratinocytes, endothelial and mononuclear cell types and S. pyogenes counts.